Réduction et intégration de prédications : paramètres pour l'analyse des co-prédications adjectivantes - Eva Havu; Michel Pierrard (Discours)
This paper proposes a basis for the description of the numerous parameters governing the extension and flexibility of constructions classified as adjectival co-predications: [1] adjuncts, [2] direct object complements introduced by occasionally predicative verbs, by verbs taking propositional complements and by stative causative verbs, [3] indirect object complements introduced by a preposition or by comme, [4] the predicative uses of avoir and [5] de adj constructions. The approach is based on two types of parameters describing the different degrees of connection between propositions (cf. Lehmann [1989]): a) the degree of reduction of the co-predication enables the definition of its intrapredicative cohesion in different constructions; b) the degree of integration of the co-predication in the main predication determines the interpredicative cohesion between the predications.